2021
DOI: 10.1097/ta.0000000000003253
|View full text |Cite
|
Sign up to set email alerts
|

Critical traumatic brain injury is associated with worse coagulopathy

Abstract: As thromboelastography (TEG) becomes the standard of care in patients with hemorrhagic shock (HS), an association between concomitant traumatic brain injury (TBI) and coagulopathy by TEG parameters is not well understood and is thus investigated. METHODS:Retrospective analysis of trauma registry data at a single level 1 trauma center of 772 patients admitted with head Abbreviated Injury Scale (AIS) score of 3 and TEG studies between 2014 and 2017. Patients were stratified to moderate-severe TBI by head AIS sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…2), suggesting that the platelet, an essential hemostatic ingredient, may contribute to thrombosis. It was recently demonstrated that critical TBI correlates with a signi cant worsening of traumatic coagulopathy in comparison with moderate/severe TBI [72]. Surprisingly, even our patients were severely injured, all the coagulation pro le was undistinguishable between the patients with and without DVT (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…2), suggesting that the platelet, an essential hemostatic ingredient, may contribute to thrombosis. It was recently demonstrated that critical TBI correlates with a signi cant worsening of traumatic coagulopathy in comparison with moderate/severe TBI [72]. Surprisingly, even our patients were severely injured, all the coagulation pro le was undistinguishable between the patients with and without DVT (Fig.…”
Section: Discussionmentioning
confidence: 59%
“… 35 The cause of death in a majority of patients in our cohort was due to TBI. Although TBI is associated with an inherent coagulopathy, 36 the results from this investigation may not be applicable to all trauma patients. It is possible that low fibrinogen is simply a specific marker of injury severity in patients with severe TBI that is not captured by other traditional measures of coagulopathy, such as INR.…”
Section: Discussionmentioning
confidence: 95%
“…As far as we know, this study is the largest cohort to date to examine the role of head and extra-head injuries and their association in the development of coagulopathy in trauma patients. All degrees of TBI severity, from mild (AIS head = 1) to currently untreatable (AIS head = 6) were included herein, whereas many previous studies restricted their analysis to moderate-to-severe TBI patients (excluding AIS head values of 0-1 and 6) (10,21,22). Moreover, all types of extracranial lesions associated to TBI, from none to extremely severe, were also included in the present study.…”
Section: Mainmentioning
confidence: 99%